Unleashing the Potential of 5G for Smart Cities: A Focus on Real-Time Digital Twin Integration - Afsaana Sultaana Mahomed; Akshay Kumar Saha (Smart Cities)
The arrival of 5G technology is transforming the creation of smart cities by delivering unmatched speed, extremely low latency, and broad device connectivity. These developments allow for the effortless integration of IoT devices, live monitoring systems, and cutting-edge urban applications. This paper examines the impact of 5G in tackling significant urban challenges, including network overload, energy efficacy, and data security, while highlighting its revolutionary potential in improving smart city frameworks. An important emphasis is the fusion of 5G with real-time digital twins, which link physical and digital realms to enhance urban systems, refine resource management, and strengthen public safety. Even with its potential, the rollout of 5G encounters challenges such as expensive infrastructure, significant energy requirements, and limited signal reach. This research explores the present trends, current applications, and new challenges related to 5G in smart cities, providing insights into its constraints and approaches to address them. It summarizes the necessity of cooperation among stakeholders to realize 5G’s complete capabilities and to create scalable, secure, and sustainable solutions for smart cities.